Analysis of macrofungal communities reveals a complex reciprocal influence between Mediterranean montane calcareous grassland and surrounding forest habitats. Issue 2 (20th April 2020) - Pecoraro, Lorenzo; Caruso, Tancredi; Kumar Gupta, Vijai; Borris, Robert P.; Zhang, Yun‐Chun; Cai, Lei
Abstract: Fungi are essential components of all terrestrial ecosystems. Despite the crucial ecological role of soil fungi in grasslands, knowledge about fungal community diversity and structure in Mediterranean meadow habitats is still fragmentary. We analyzed macrofungal communities in three geographically distinct Mediterranean montane calcareous grasslands and surrounding forests, by means of fruit body surveys. We investigated a number of biotic and abiotic factors influencing the studied fungal communities, including plant species composition. Out of 6365 fruit bodies, a total of 268 species belonging to 84 genera were found. In general, there was a significant correlation between plant species richness and fungal richness. Variation in vegetation and plant community structure accounted for approximately 20% of variance in fungal community structure. Tree and shrub vegetation played a dominant role in shaping the analyzed fungal communities, both in meadows and surrounding forests, with particular influence on ectomycorrhizal, litter, and lignicolous saprotrophic fungi. Fungal biodiversity in the studied meadows was increased by the presence of tree and shrub species from the adjacent forests, but was reduced by the increasing vegetation cover.